A COMPREHENSIVE AND HOLISTIC DIAGNOSTIC APPROACH IN A PATIENT WITH TORSION CYST: A CASE REPORT - Tirtana, I Made Dwi; Christyani, Fenyta; Wardani, AA Eka (Lux Mensana: Journal of Scientific Health, 2024)
Ovarian torsion is one of the most common causes of adnexal abdominal pain. In this case, we report A 38-years old woman, P2002, who has been suffering from acute lower abdominal pain and a developing abdominal mass for the past year. Other complaints like fever or vaginal discharge were denied. Her last menstrual period (LMP) was one week ago. Transvaginal ultrasound examination showed a hypoechoic picture measuring 6.16 cm x 6.07 cm with a Whirpool sign (+) on left adnexa. She was diagnosed with ovarian cyst torsion. The patient then underwent a laparotomy cystectomy.